2023
DOI: 10.1039/d2tc04820e
|View full text |Cite
|
Sign up to set email alerts
|

Solution processable carbazole-benzophenone derivatives as bipolar hosts enabling high-efficiency stable green TADF organic LEDs

Abstract: Solution-processable bipolar materials acting as hosts, soluble in common organic solvents, are key materials for thermally activated delayed fluorescence (TADF) emitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Grigalevicius et al demonstrated two new carbazole-benzophenone derivatives ( BPBCzO and BCzBCzO ) as bipolar hosts, employing carbazole as an electron donor and benzophenone as an electron acceptor (Scheme 3). 29 The E T of the host materials ( BPBCzO and BCzBCzO ) was 2.64 and 2.60 eV, respectively. BCzBCzO showed higher thermal stability than BPBCzO because of its higher molecular weight.…”
Section: Small Molecules As Host Materialsmentioning
confidence: 97%
See 4 more Smart Citations
“…Grigalevicius et al demonstrated two new carbazole-benzophenone derivatives ( BPBCzO and BCzBCzO ) as bipolar hosts, employing carbazole as an electron donor and benzophenone as an electron acceptor (Scheme 3). 29 The E T of the host materials ( BPBCzO and BCzBCzO ) was 2.64 and 2.60 eV, respectively. BCzBCzO showed higher thermal stability than BPBCzO because of its higher molecular weight.…”
Section: Small Molecules As Host Materialsmentioning
confidence: 97%
“…The design strategies, photophysical properties and electroluminescent performance data of solution-processed small molecule hosts are discussed below. 19–31…”
Section: Small Molecules As Host Materialsmentioning
confidence: 99%
See 3 more Smart Citations